2013
DOI: 10.2466/02.07.pr0.112.3.706-715
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Personality: Understanding Their Relationship to Health Resilience

Abstract: A growing body of research suggests there are important relationships among spirituality, certain personality traits, and health (organismic) resilience. In the present study, 83 college students from two southeastern universities completed a demographic questionnaire, the NEO Five Factor Inventory, and the Resilience Questionnaire. The Organismic resilience and Relationship with something greater subscales of the Resilience Questionnaire were used for analyses. Health resilience was associated with four of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…Individuals higher on agreeableness make more social investments in work, family, religion, and other prosocial activities (Saadullah & Bailey, 2014). Agreeableness has also been found to relate highly to spirituality (Womble et al, 2013), religious values (Wisker & Rosinaite, 2016), and religiosity (Aghababaei, 2013). Individuals who have strong belief in spirituality and religiosity have been found to possess high agreeableness and conscientiousness (Aghababaei, Błachnio, Arji, Chiniforoushan, Tekke, & Mehrabadi, 2015).…”
Section: Agreeablenessmentioning
confidence: 99%
“…Individuals higher on agreeableness make more social investments in work, family, religion, and other prosocial activities (Saadullah & Bailey, 2014). Agreeableness has also been found to relate highly to spirituality (Womble et al, 2013), religious values (Wisker & Rosinaite, 2016), and religiosity (Aghababaei, 2013). Individuals who have strong belief in spirituality and religiosity have been found to possess high agreeableness and conscientiousness (Aghababaei, Błachnio, Arji, Chiniforoushan, Tekke, & Mehrabadi, 2015).…”
Section: Agreeablenessmentioning
confidence: 99%
“…Most of the research that is so far made in general population and using NEO-PI/Five factor model of personality, showed mixed results. Womble showed that spirituality and neuroticism shared 43 % of variance of resilience in college students (Womble et al 2013), similar as in work of Lockenhoff in HIV population (Löckenhoff et al 2009). Johnstone stated that spiritual variables add little to mental health in the sample of individuals with different faith traditions (Johnstone et al 2012).…”
Section: Discussionmentioning
confidence: 81%
“…Previous research has suggested that religiosity and spirituality are related to several psychological traits (Gartner, ; Labbe & Fobes, ; Womble et al, ). We examined the relationship between spirituality and two traits (self‐confidence and personal control) and found that spirituality affects peoples’ behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Although personal spirituality could potentially be related to many variables in different areas, we sought to identify a few key variables as potential correlates of personal spirituality that could help us demonstrate predictive validity of the personal spirituality construct. Many researchers have investigated the relationship between spirituality and other variables including demographic variables (e.g., Shahabi et al, 2002;Zinnbauer et al, 1997), psychological traits (Labbe & Fobes, 2010;Womble, Labbe, & Cochran, 2013), and specific behaviors (Bekkers & Wiepking, 2011). In this study, we wanted to test for the validity of the new personal spirituality scale by specifically examining its correlates across countries.…”
Section: Predictive Validity Of Personal Spiritualitymentioning
confidence: 99%